Demand regimes and the business-cycle: Feedback effects between capacity utilization and income distribution taking into account overhead labor - SVAR-estimates for Germany (2007 - 2021) - Mads R. Hansen (Hochschule für Wirtschaft und Recht Berlin, Institute for International Political Economy (IPE), 2024)
In this paper, Structural Vector Autoregressive (SVAR) models of quarterly data between 2007 and 2021 are estimated to assess short-term regimes of aggregate demand and distribution in Germany. The obtained Impulse Response Functions (IRFs) of the conventional neo-Goodwinian baseline case, with an aggregate wage-share, are compared to an alternative model, disaggregating the wage-share. The robustness of the results is tested by imposing an alternative post-Kaleckian ordering of (contemporaneous) causation. For the neo-Goodwinian baseline model, a profit-led demand schedule and a pro-cyclical wage-share are found. Disaggregation reveals, however, that the pro-cyclical wage-share is mainly driven by supervisory wages, while positive shocks in the direct wage-share had a stronger (negative) impact on aggregate demand, than the supervisory wage share. Imposing post-Kaleckian restrictions of causation yields a consistent (although weaker) estimate of the demand-regime but reversed distributive regimes: The aggregated wage-share behaves counter-cyclical, with the supervisory wage-share reacting stronger (negative) than the direct wage share, when subject to a positive shock in capacity utilization.
Keywords: E12; E25; E6; 330; Demand Regime; Aggregate Demand; Distribution; Capacity Utilization; Business Cycle; SVAR; Functional Income Distribution; Overhead Labor; Germany